PERBAIKAN INSTALASI LISTRIK DAN PEMASANGAN SAKLAR OTOMATIS PHOTO CONTROL SENSOR LAMPU PENERANGAN DI MASJID RIYADUS SOLIHIN KAMPUNG KEBON DUREN RT 03 / RW 04 KELURAHAN KALIMULYA KECAMATAN CILODONG KOTA DEPOK - yusyama, asep yana (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2020)
The title of Community Service Activities is "Repair of Electrical Installations and Installation of Automatic Switches for Photo Control Light Sensors at the Riyadus Solihin Mosque, Kebon Duren Village RT 03 / RW 04 Kelurahan Kalimulya Cilodong District, Depok City." This activity is based on the aim of improving public facilities and infrastructure, in this case the Riyadus Solihin Mosque in the electricity sector to support religious activities carried out by the surrounding community. This activity will provide education to the surrounding community about the importance of maintaining the safety of lighting electrical installations and the use of energy-efficient lamps through repairing damaged electrical installations and installing energy-saving automatic switches. The expected results with the repair of electrical installations will contribute to the safety and tidiness of electrical installations with maintained continuity. In addition, this activity also carried out the installation of an automatic light switch that functions to turn on and turn off the lighting so that it will save electrical energy in an era where the economic needs of society are increasing today.